Source-to-sink analysis of ancient sedimentary systems using a subsurface case study from the Møre-Trøndelag area of southern Norway: Part 1 - depositional setting and fan evolution - Somme,TO; Jackson,CAL; Vaksdal,M (Basin Research, 2013)
In this study we use seismic reflection, well and core data to investigate the role that basin physiography and sediment routing systems played on the distribution, geometry and stratigraphic architecture of Upper Cretaceous submarine fans offshore Norway. The Late Cretaceous Møre-Trøndelag margin of western Norway was characterised by steep submarine slopes (gradient of ~0,3-3º). Mudstones dominate the Upper Cretaceous slope succession although a few regionally extensive, sandstone-dominated units are developed. We focus on the most regionally extensive sandstone unit, which is of Late Turonian-to-Early Coniacian age. Mapping and visualisation of 2D and 3D seismic reflection data and analysis of well data indicates that the sandstone unit comprises a total of 11 submarine fans, which were fed by sand-rich sediment gravity flows routed through multiple upper slope canyons. Based on the internal organisation of seismic facies, four fan types have been identified: (i) Type Ia fans, which are characterised by <10 erosional channel complexes at their bases and aggradational to landward-stepping lobes in their upper parts; (ii) Type Ib fans, which are characterised by >10 erosional channel complexes at their bases and aggradational to landward-stepping lobe and mass-transport deposits near the fan apex in their upper parts; (iii) Type II fans, which are dominated by aggradational lobe deposits; and (iv) Type III fans, which are dominated by a single channel complex that passes downdip into a small terminal lobe. The different fan types are interpreted to reflect variable stratigraphic responses to source proximity and basin physiography, which is principally related to the degree of local fault reactivation and differential compaction. This variability highlights the diversity of fan types that may occur over short distances along continental margins, and demonstrates the importance of local controls in understanding the internal stratigraphic va